Bölgesel Kalkınma Ajansları ve Bölgesel Eşitsizlik Üzerine Etkisi - Vurucu, Aslı Nazlı (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / İktisat Anabilim Dalı / Yönetim Ekonomisi Bilim Dalı, 2013)
Sanayi Devrimi ile temelleri atılan üretimin modern anlamda yeniden tanımlanması süreci başta sanayileşme yolunda hızla ilerleyen Batı ülkelerinde ardından tüm dünyada ülke içi gelişmişlik farklarının ortaya çıkmasına sebep olmuş, ülkeler bu farkları ortadan kaldırabilmek ve ulusal çapta kalkınabilmek için çeşitli politikalar geliştirmişlerdir. Zaman içinde kapsamları ve hedefleri değişmekle birlikte, bölgesel kalkınma politikaları, halen gelişmişlik farklarının ortadan kaldırılması ve ülke içindeki farklı yörelerin ulusal kalkınma atılımına katkılarını azami seviyeye çıkarma şeklinde iki temel amaçla uygulanmaktadırlar. Ancak son yıllarda küresel üretim sisteminde yaşanan değişimin de etkisiyle özellikle gelişmiş ülkeler tüm ülkeyi baz alan ulusal kalkınma politikalarını terk ederek bölgesel kalkınma politikalarına yönelmişlerdir. Uzun yıllar gelişmiş ülkelerin birçoğunda bölgesel gelişme için faaliyet gösteren `Bölgesel Kalkınma Ajansları? ülkemizde 2006 yılında yürürlüğe giren 5449 sayılı Kalkınma Ajansları?nın Kuruluşu, Koordinasyonu ve Görevleri Hakkında Kanun ile yasal zemine kavuşmuştur. 2009 yılında ise tüm Türkiye?de 26 istatistiki bölge kurulmasıyla kuruluşu tamamlanarak ekonomik ve sosyal alandaki faaliyetlerine başlamıştır.

As conclusive as it is in defining the modern society and production methods, the industrial revolution took a toll from nations climbing the steps of progress by creating regional inequalities that stem from unevenly applied or insufficiently planned growth policies. First among Western nations and globally afterwards, this trend continued until the emergence of the term `regional development?, which allowed national governments to recognize and address the needs of a region, province or any other specific area within their national boundries. Although varying in terms of methods and goals, almost all regional development policies share the two same basic principles; to eradicate interregional disparity and maximize the output of a certain region?s contribution to the national development. In effect until recently, this policy is slowly evolving into an even more region-centric approach as the regional administrations and their locally developed and applied policies began to outweigh national governments and their centrally-controlled development goals. Relatively late in introducing the concept of regional development, Turkey laid the legal basis of regional development first in 2006 with the enactment of the Law On The Establishment And Duties of Development Agencies, to be completed in 2009 with the establishment of 26 regional development agencies tasked with planning and running various local economic and social development programs.
Regional Development Agencies and Their Impact on Regional Inequality
Keywords: Ekonomi; Economics